2022
DOI: 10.3390/biom12030462
|View full text |Cite
|
Sign up to set email alerts
|

The Role of LSD1 and LSD2 in Cancers of the Gastrointestinal System: An Update

Abstract: Epigenetic mechanisms are known to play a key role in cancer progression. Specifically, histone methylation involves reversible post-translational modification of histones that govern chromatin structure remodelling, genomic imprinting, gene expression, DNA damage repair, and meiotic crossover recombination, among other chromatin-based activities. Demethylases are enzymes that catalyse the demethylation of their substrate using a flavin adenine dinucleotide-dependent amine oxidation process. Lysine-specific de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…In human cells, overexpression of LSD1 is involved in the proliferation, inhibition of apoptosis, and metastasis of several types of cancers, such as gastric, breast, and prostate cancers [ 109 , 118 , 119 ]. The elevated levels of Lsd1/2 proteins at 37°C suggest that their functions might be essential for cell survival at stressful high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In human cells, overexpression of LSD1 is involved in the proliferation, inhibition of apoptosis, and metastasis of several types of cancers, such as gastric, breast, and prostate cancers [ 109 , 118 , 119 ]. The elevated levels of Lsd1/2 proteins at 37°C suggest that their functions might be essential for cell survival at stressful high temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…In a comprehensive study focusing on liver cancer, HCC (Hepatocellular Carcinoma) cell lines were found to exhibit elevated levels of LSD2. Bayo et al employed various methodologies to identify potential therapeutic targets associated with epigenetic alterations in these cancer cells [30,31]. Previously, it was reported that patients with high tumor expression levels of EZH-2, EHMT2/G9a, KDM3A, KDM4B, and LSD1/KDM1A had significantly worse prognoses [30].…”
Section: Liver Cancer Cellsmentioning
confidence: 99%
“…During inflammation, LSD1 can act as both a pro-inflammatory and anti-inflammatory epigenetic regulator [ 42 ]. LSD1 can have pro-inflammatory effects, and upregulation can contribute to rheumatoid arthritis, sepsis, hepatitis B virus-associated glomerulonephritis (HBV-GN) and SARS-CoV-2 infection, as well as tumor progression [ 157 ]. It needs to be clarified which of these effects are mediated by MR, as LSD1 acts as coregulator for several NRs.…”
Section: Mr Signaling and Micromilieumentioning
confidence: 99%